How Procedural and Informational Justice Moderated by Organizational Collectivism Predict Employee Organizational Commitment - Mahadianto, Moh Yudi; Muhammad Siddiq, Dedi; Mamat, Mazlina; Abu Bakar, Hatinah; Edy Hartono (International Research Journal of Business Studies, 2025)
This study tested the perceived procedural and informational justices in predicting commitment among employees at rural banking sector. The paper assumes that the direct link of perceived procedural and informational justices with organizational commitment is moderated by organizational collectivism. For this end, the study used a survey method and analyses using Partial Least Squares 3 (PLS- SEM) from 284 Indonesian rural bank employees in Indonesia. The results suggest the following. First, procedural, and informational justice are two predictors of employee commitment to organizations. Second,  organizational collectivism significantly moderates the relationship between procedural justice and employee commitment, but failed to moderate the relationship between informational justice and employee commitment. This study is the first one to examine the moderating effect of organizational collectivism on the relationship between procedural and informational justice with employee commitment.